2013
DOI: 10.1002/htj.21089
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Heat Transfer Augmentation in a Circular Tube Fitted with Alternative Axis Twisted Tape in Laminar Flow under a Constant Heat Flux

Abstract: CFD simulation of heat transfer and friction factor characteristics in a circular tube fitted with twisted tape inserts in laminar flow and constant heat flux is conducted using FLUENT version 6.3.26. Plain and alternate axis twisted tape inserts with twist ratios (y = 2.93, 3.91, 4.89) and alternative angles (β = 30°, 60°, 90°) have been used for the simulation. The simulated results are matched with the literature correlations for a plain tube with a discrepancy of less than ±8% for Nusselt number and ±6.25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the work of Salman et al [25], it was discovered numerically that heat transfer in a plain tube can be enhanced by fitting an alternate-axis twisted tape or a plain twisted tape into the plain tube.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Salman et al [25], it was discovered numerically that heat transfer in a plain tube can be enhanced by fitting an alternate-axis twisted tape or a plain twisted tape into the plain tube.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that heat transfer coefficient significantly increased with decreasing cut depth. Salman et al [5] also studied the behaviors of heat transfer and friction factor in a tube equipped with twisted tape inserts with different alternative angles ( = 30 o , 60 o and 90 o ). For their studied range, heat transfer coefficient increased with increasing alternative angle.…”
Section: Introductionmentioning
confidence: 97%
“…Various researchers have performed the experiments on the thermal performance of various corrugated tubes with pitch ranges from 2 to 64 mm. Studies have also been done for the various diameter ratios range from 0.31 to 0.59.…”
Section: Introductionmentioning
confidence: 99%